Critical behavior of La0.75Sr0.25MnO3 - COEY, JOHN MICHAEL DAVID (American Physical Society, 2002)
Magnetization, susceptibility, and specific heat measurements were made on a single crystal of La0.75Sr0.25MnO3. The ferromagnetic-to-paramagnetic phase transition was found at 346 K and four critical exponents were measured as: ??=0.05??0.07, ?_=0.40??0.02, ?_=1.27??0.06, and ??=4.12??0.33. The values of critical exponents are all between mean-field values and three-dimensional-(3D)-Ising-model values. The scaling behavior is well obeyed for all measurements, and the associated exponent relations are well satisfied, validating the critical analysis. Although the cubic crystal structure of this material makes the 3D Heisenberg the expected model, uniaxial magnetic anisotropy arising from the shape of the sample causes the 3D Ising model to be important within the experimental temperature range.
PUBLISHED
Keywords: Physics